The theatre of cruelty aesthetics: Does life in society has to be beautiful or good? - Barroso, Paulo (2011)
With this abstract I intend to reflect on the implications between individuals and society, starting from the question “Does life in society has to be beautiful or good?” For this, I support my paper on the work of Franz Kafka, In The Penal Colony, to represent a social theater of cruelty aesthetics in contemporary societies of post-modernity. The social dimension of ethics is a sort of practice of cruelty as well as a sort of aesthetics representing prescriptions of society, which clashes with the contemporary trends of these post-modern societies characterized by the individualism, narcissism, consumption and media spectacle. The theater of cruelty works on punishing the condemned; it is essentially a work of social aesthetics or hygienist ethics. The insensitive machine of Law has social authority and it embodies the faults or the mistakes punished in Kafka’s writing. Is this machine still working (in an invisible way) in our societies, where the social requirements remain the order of the Law?